2020
DOI: 10.1177/0363546520951815
|View full text |Cite
|
Sign up to set email alerts
|

Soaking of Autologous Tendon Grafts in Vancomycin Before Implantation Does Not Lead to Tenocyte Cytotoxicity

Abstract: Background: Surgical site infections (SSIs) after anterior cruciate ligament (ACL) reconstruction procedures are an unfortunate complication. Soaking grafts in vancomycin before implantation has been reported to reduce the incidence of postoperative SSI after ACL reconstruction. There is potential for vancomycin to compromise graft integrity because of tenocyte toxicity. Purpose: To examine the in vitro toxicity of varying doses of vancomycin on human tenocytes. Study Design: Controlled laboratory study. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…There were no significant changes in tenocyte viability after 2 and 6 hours of incubation at any vancomycin concentration between 0 and 12,800 µg/mL. Incubation with vancomycin for 24 hours led to a significant decrease in cell viability at higher concentrations 13 .…”
Section: Molecular Insightsmentioning
confidence: 75%
“…There were no significant changes in tenocyte viability after 2 and 6 hours of incubation at any vancomycin concentration between 0 and 12,800 µg/mL. Incubation with vancomycin for 24 hours led to a significant decrease in cell viability at higher concentrations 13 .…”
Section: Molecular Insightsmentioning
confidence: 75%
“…Comparable results have been shown for porcine flexor digitorum profundus tendons and human semitendinosus grafts, and even relatively high concentrations of vancomycin did not show significant cell death and toxicity in human tenocytes derived from human patellar tendons. [7][8][9] Evaluating this data, it can be stated with high confidence that at the time of implantation, vancomycin soaking does not affect the biomechanical properties of the various ACL grafts.…”
Section: See Related Article On Page 953mentioning
confidence: 82%
“…Statistically significant fewer infections (0.013% vs. 0.77%, p , 0.001) were observed in patients who had graft treatment with vancomycin (7,507 subjects) compared with the controls (13,861 subjects) 35 . Two of these studies analyzed patient-reported outcome measures, and IKDC scores showed no difference for patients in the vancomycin group and control group at 1 year postoperatively 35 . Overall, the vancomycin wrap has been effective in ACLR procedures because of its safety profile, low allergenicity, heat stability, and large volume of distribution 36 .…”
Section: Sports-primary Andmentioning
confidence: 87%